Stabilisation measures on the de-occupied territories: conceptual interpretation, classification, and application features - K. L. Buhaichuk (Law and Safety)
The publication provides a scientific analysis of the “stabilisation measures” concept which has recently been used to determine the specifics of public authorities and law enforcement agencies' activities on the de-occupied territories of our country. It has been proved that the concept of “stabilisation measures” arose in the course of NATO peacekeeping operations in the Balkans and is primarily associated with law enforcement activities of specially authorised military units capable of performing police functions. According to NATO’s Joint Doctrine (AJP-3.22), stabilisation measures are defined as special activities aimed at strengthening or providing temporary replacement for local police forces to help restore and/or maintain public order and security, the rule of law and the protection of human rights.